INFLUENCING OF TRANSFORMATIONAL LEADERSHIP ON ARCHITECT’S JOB SATISFACTION AND TURNOVER INTENTION: MEDIATED BY QUALITY OF WORK LIFE (QOWL) - Firstaria, Dania; Anggiani, Sarfilianty (PEOPLE: International Journal of Social Sciences, 2020)
The architectural consulting service industry known has the long working hours and frequent overtime activities. This condition can be one of the problems that continue happen that can be impacted to turnover intention in a company. The purpose of this study is to analyze all variables namely transformational leadership, quality of work life (QoWL), job satisfaction and turnover intention. Also, to analyze the effects of transformational leadership on job satisfaction and turnover intention that mediated by QoWL. The data collected through primary data by questionnaire that answered by 215 Architect Employees who work in Architecture Consultants in Jakarta Indonesia. for analysis the hypotheses used Structural Equation Model. The findings in this study are the work performances influenced by how the employee’s performance and how much HR in the company. The high and low number of qualified workers in the company influenced by the QoWL of employees which will impact the company successful itself. The implications obtained in this study which transformational leader needs to increase job satisfaction in order for reducing turnover intention that can be mediated by quality of work life (QoWL).